Pou2f2 Regulates the Distribution of Dorsal Interneurons in the Mouse Developing Spinal Cord - Gauhar Masgutova; Audrey Harris; Benvenuto Jacob; Lynn M. Corcoran; Frédéric Clotman (Frontiers in Molecular Neuroscience, 2019)
Spinal dorsal interneurons, which are generated during embryonic development, relay and process sensory inputs from the periphery to the central nervous system. Proper integration of these cells into neuronal circuitry depends on their correct positioning within the spinal parenchyma. Molecular cues that control neuronal migration have been extensively characterized but the genetic programs that regulate their production remain poorly investigated. Onecut (OC) transcription factors have been shown to control the migration of the dorsal interneurons (dINs) during spinal cord development. Here, we report that the OC factors moderate the expression of Pou2f2, a transcription factor essential for B-cell differentiation, in spinal dINs. Overexpression or inactivation of Pou2f2 leads to alterations in the differentiation of dI2, dI3 and Phox2a-positive dI5 populations and to defects in the distribution of dI2-dI6 interneurons. Thus, an OC-Pou2f2 genetic cascade regulates adequate diversification and distribution of dINs during embryonic development.